Adsorption and catalytic oxidation of arsenite on Fe-Mn nodules in the presence of oxygen. (November 2020) - Rady, Omar; Liu, Lihu; Yang, Xiong; Tang, Xianjin; Tan, Wenfeng; Qiu, Guohong
Abstract: Fe-Mn nodules affect the speciation, transformation and migration of arsenic (As) via redox and adsorption reactions. However, few studies have been concerned with their interaction in the presence of dissolved oxygen. In this work, the interaction mechanism of As(III) and Fe-Mn nodules was studied in different atmospheres. The influence of pH, dissolved oxygen concentration and chemical composition of nodules on the reaction was also investigated. The results indicated that manganese oxides and iron oxides in nodules respectively contribute to As(III) oxidation and As(III, V) adsorption. Under oxic conditions, Fe-Mn nodules acted as a catalyst to accelerate the oxidation of Mn(II) to Mn(III, V) oxides, which significantly enhanced As(III) oxidation. In the system containing 10 mg L −1 As(III) and 1.0 g L −1 Fe-Mn nodules, the maximum oxidation capacity of As(III) reached 3.22, 3.48 and 3.71 mg g −1, and the corresponding As(III, V) adsorption capacity reached 2.49, 2.40, and 2.39 mg g −1 in nitrogen, air and oxygen atmosphere, respectively. The oxidation capacity of As(III) increased and decreased with increasing dissolved oxygen concentration and pH, respectively. This work clarifies the mechanism of As(III) oxidation by soil Fe-Mn nodules in various systems and contributes to a better understanding of the behaviors and fate of As in environments. Graphical abstract: Image 1 Highlights: Fe-Mn nodules can effectively oxidize and adsorb As(III). Fe-Mn nodules work as a catalyst for As(III) oxidation in the presence of oxygen. Mn(III, IV) oxides generated from Mn(II) oxidation accelerate As(III) oxidation. Manganese oxides in Fe-Mn nodules contribute much to As(III) oxidation. Iron oxides in Fe-Mn nodules play an important role in As(V) adsorption.